The Evaluation of Hole Mobility Characteristics with Surface Roughness - Shin, Hyeseon; Lim, Kyungsuk; Hwang, Shinae; Han, Il-Ki; Jang, Moongyu (AMER SCIENTIFIC PUBLISHERS, 2017)
Hole mobility characteristics were investigated as a function of the temperature and effective field with surface roughness. The temperature varied from 80 K to 340 K and from 93 K to 533 K in Hall effect measurement and variable temperature probe station measurement, respectively. From the Hall effect measurement in bulk silicon, there was no difference of hole mobility in either the roughness controlled or the roughened samples. In SOI substrate, the hole mobility measured by transconductance showed dominant phonon scattering dependence at high effective field. In addition, the hole mobility was severely decreased at the roughened sample with the increase of temperature due to the increased phonon and surface roughness scattering. Surface roughness scattering was dominant at high effective field and was expected to be dominant at low temperature.
Keywords: INVERSION LAYER MOBILITY; SI-MOSFETS; TRANSISTORS; ELECTRON